Dissociative symptoms in school-aged adopted children who experienced maternal separation and disruptive caregiving in infancy - Winnette, Petra; Bob, Petr; Datta, Ashley (Frontiers in Psychiatry, 2025)
Amounting findings on maternal separation and early disturbed caregiving suggest that this type of early experience negatively influences socioemotional development and may be associated with behavioral and mental health problems in later life. Concerning previously published studies, we have assessed if maternal separation and disrupted caregiving before adoption in infancy could be related to heightened levels of dissociative symptoms and behavioral problems in middle childhood. We involved 30 children (sample S1) who had experienced maternal separation after birth and short-term institutional or foster care prior to adoption before 16.7 months of age. Based on the parents’ reports, they had not experienced any other significant adversities by the time of evaluation. These children were compared to a control group of children who have lived with their biological mothers in complete families (sample S2; N = 25). Although the findings are correlational and not causal, they indicate that specific adverse experiences, maternal separation after birth, and relatively short disruptive caregiving prior to successful adoption in infancy could be associated with significantly heightened levels of dissociative symptoms and behavioral problems in school-aged children. Our data also contribute to the literature on child socioemotional development and the etiology of dissociative disorders.